Persepsi Siswa dan Guru tentang Pembelajaran PAI di Era New Normal: Intensitas dan Keberhasilan Belajar - Sunarto; Abdulloh Hadziq (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
In the new normal era, Islamic Religious Education (PAI) learning has undergone significant changes that have an impact on student learning success. This study aims to determine the relationship between students' and teachers' perceptions of Islamic Education learning in the new normal era with students' learning intensity and its impact on students' learning success. The research method used is quantitative with multiple linear regression analysis. The results showed a t-test that had been carried out by getting a significant value of student perceptions (sig = 0.000) and teacher perceptions (sig = 0.002). SE (effective contribution) value of students (19.90) and teachers (27.9) about PAI learning in Era new normal with learning success. The t test that has been carried out gets a significant of 0.000. SE value (effective contribution X2: learning intensity (17.4) (49.4) impact on student learning success. The simultaneous F test that has been carried out is significant at 0.000. The value of the relationship obtained by perception and learning intensity with student learning success (28.3%). The conclusion from the research results is that there is a significant relationship between X2 and Y.